2021
DOI: 10.1002/jnr.24864
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors SIX3 and VAX1 are required for suprachiasmatic nucleus circadian output and fertility in female mice

Abstract: The homeodomain transcription factors sine oculis homeobox 3 (Six3) and ventral anterior homeobox 1 (Vax1) are required for brain development. Their expression in specific brain areas is maintained in adulthood, where their functions are poorly understood. To identify the roles of Six3 and Vax1 in neurons, we conditionally deleted each gene using Synapsin cre , a promoter targeting maturing neurons, and generated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 85 publications
5
26
0
Order By: Relevance
“…Indeed, as can be observed on the individual actigraphy data from 6 controls and 8 Six3 syn males ( Supplementary Figure 1 ), the activity onset of the controls during DD was relatively variable, suggesting the Six3 fl/fl allele by itself impacts SCN function. Interestingly, as we had previously observed for Six3 syn females [ 25 ], 6/8 Six3 syn males on DD had very variable activity periods, where they initially trended to have a period shorter than 24 h, but after variable times on DD, suddenly switched to a longer Tau. Owing to the low activity profile of some of the Six3 syn males ( Supplementary Figure 1 , Six3 syn ), we were unable to analyze the data from some of the mice.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Indeed, as can be observed on the individual actigraphy data from 6 controls and 8 Six3 syn males ( Supplementary Figure 1 ), the activity onset of the controls during DD was relatively variable, suggesting the Six3 fl/fl allele by itself impacts SCN function. Interestingly, as we had previously observed for Six3 syn females [ 25 ], 6/8 Six3 syn males on DD had very variable activity periods, where they initially trended to have a period shorter than 24 h, but after variable times on DD, suddenly switched to a longer Tau. Owing to the low activity profile of some of the Six3 syn males ( Supplementary Figure 1 , Six3 syn ), we were unable to analyze the data from some of the mice.…”
Section: Resultssupporting
confidence: 67%
“…We recently showed that the Synapsin cre -allele recombines the Six3 flox -allele throughout the brain including the SCN, impairing SCN circadian output in Six3 syn females [ 25 ]. To determine whether circadian function was also weakened in Six3 syn males, we placed Six3 fl/fl and Six3 syn males on running-wheels ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations